FACTORS THAT CONTRIBUTE TO ENGLISH INVERSION INTRICACIES AMONG GRADE TWELVE LEARNERS - Nicholas Bwalya; Pethias Siame; Djalilova Malika Shuxratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This study investigates the factors that contribute to the intricacies of English inversion among Grade Twelve students at Nkulumashiba Secondary and Mikomfwa Secondary Schools in Luanshya District, Zambia. It aims to identify and evaluate persistent challenges identified in Examinations Council of Zambia reports from 2019 to 2022, which indicate poor student performance in grammatical structures such as inversion. The research involved 30 purposively selected students and 6 teachers, with data presented qualitatively. The study is framed within the theoretical perspectives of Generative Grammar and Second Language Acquisition. Key findings reveal several factors that contribute to inversion difficulties which include the following, a lack of in-depth knowledge by teachers, a shortage of teaching and learning materials as well as reliance on unguided internet resources. The reliance on unguided internet sources often results in the dissemination of incorrect information which further complicates students’ understanding of inversion rules. Additionally, the study highlights an unfavorable learning environment, characterized by inadequate instructional methods and limited access to educational resources. The research uncovers a pervasive lack of knowledge among students and a significant gap in teachers’ understanding of inversion concepts which contributes to poor student performance. These findings underscore the need for improved teacher training, enhanced teaching methodologies, and the development of comprehensive teaching materials to address the identified challenges. Addressing the above issues would improve English language proficiency and examination outcomes for Grade Twelve students in Zambia.